The use of multimodality in English grammar teaching in eighth-grade textbooks in Finland in the 21st century - Myhrberg, Joanna (My University, 2026)
This thesis examines the use of multimodal elements in textbook grammar instruction for eight-grade students in Finland. Multimodality refers to the use of different communication methods e.g. textual elements and pictorial elements together to present information. This thesis focuses on the benefits that pictorial elements have on grammar instruction. Analysis is conducted on how textbooks make use of multimodality when introducing ESL grammar to 8th-grade learners. Grammar teaching goals are examined in relation to multimodality in this thesis to establish a sense of proper grammar instruction. Pictorial elements are divided into four different categories based on their impact on grammar instruction. Analysis of textbooks showed that multimodal elements are not utilized to their full capacity to benefit grammar instruction. Pictorial elements that did not benefit grammar instruction were the most frequent in analyzed textbooks.
Keywords: multimodality, grammar, textbooks, English as a second language, multimedia principle